Compulsory Tax Objectives Reviewed from Factors Affecting Personal People in Paying Taxes: Case Study on Dinas Tenaga Kerja Kota Surabaya - Sari, Devi Permata (Devotion : Journal of Research and Community Service, 2023)
This study aims to analyze the influence of awareness of Taxpayers, Taxpayer knowledge, administrative sanctions, tax apparatus services, modernization of taxation system on taxpayer compliance at the Office of Manpower of Surabaya city. The data of this study were obtained from Questionnaire (Primary). Data analysis used are Validity Test, Reability Test, Normality Test, Outer Model Testing (Measurement Model), Structural Model Testing (Inner Model). The result of this research is partially awareness of Taxpayer only does not have an effect on compliance, Taxpayer's knowledge only influence to compliance, administrative sanction only does not have an effect on compliance, Tax Apparatus service does not have an effect on compliance, modernization of tax system alone does not influence to compliance.